Record of two rare taxa from Synura genus (Chrysophyceae) with a description of a new species (Synura tiksiensis sp. nov.) near the arctic settlement of Tiksi, Yakutia, Russia - Bessudova, Anna; Gabyshev, Viktor; Likhoshway, Yelena V. (Phytotaxa, 2022)
A new species Synura tiksiensis (section Petersenianae) is described based on structure of silica scales, observed by scanning and transmission electron microscopy. The new species was recovered from several ponds near the arctic settlement of Tiksi (Yakutia, Russia). Synura tiksiensis scales have a narrow keel with large pores, ending with an acute, round tip, and rounded struts with big pores connected to each other by a parallel rib. Two rare species were found in one of the studied ponds: Synura petersenii f. taymyrensis and S. obesa. The latter was discovered for the first time after the initial finding. The species reassembles S. tiksiensis in scale structure. Described Synura species were found at water temperatures between 14.6–16.7 °C and pH 7.22–7.51.